Concilier vie professionnelle et vie familiale pour promouvoir l’égalité entre les femmes et les hommes au Portugal : considerations et perspectives à la lumière de la directive 2019/1158 sur l’équilibre entre vie professionnelle et vie privée des parents et des aidants - Carvalho, Catarina de Oliveira (2021)
Directive (EU) 2019/1158 on work-life balance for parents and carers is one of the first initiatives aimed at promoting the European Pillar of Social Rights and has the merit of unequivocally formalizing the link between reconciliation of work and family life and equality between men and women with regard to labour market opportunities and treatment at work. In this paper, we will highlight some of the most relevant topics of the directive and its impact on the Portuguese framework. As it will be explained, many of the novelties introduced by directive 2019/1158 do not need formal implementation, since the Portuguese framework already goes beyond the minimum provisions of EU law. Nonetheless, there are some aspects that must lead to the amendment of the Portuguese legislation and that will surely contribute to improve reconciliation between work and family.